The problem of deformation of legal consciousness in the domestic philosophical and legal thought of the late XIX - early XX centuries - Melnyk, Mariia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The philosophical and legal approaches to understanding the essence of legal consciousness deformations in Ukrainian and Russian scientific thought of the late XIX – early XX centuries are considered. The works of such outstanding thinkers of the past as P.I. Novgorodtsev, I.A. Ilyin, N.N. Alekseev, L.I. Petrazhitsk, B.I. Kistyakovsky and others. The emphasis is made on the distinction between two types of legal consciousness – natural and positive, the mismatch between which leads to a spiritual crisis and, as a result, deformations of legal consciousness. It is noted that it is Russia that is considered the birthplace of legal nihilism. It is emphasized that the undeveloped legal awareness of the intelligentsia and ordinary people of the then Russia and Ukraine was the result of the absence of any rule of law in the everyday life of the people. The article investigates that the doctrine of the deformation of consciousness is part of the general theory of justice and began to be actively discussed since the end of the twentieth century, mainly in the territory of the former USSR. Since the theory of deformation of consciousness is under development, we turned to its origins, which can be found in the works of prominent Russian and Ukrainian great-grandchildren of the late nineteenth and early twentieth centuries. It should be noted that in this historical period Ukrainian and Russian scientific thought were closely intertwined, were in the same legal field and often eminent philosophers and lawyers, such as, for example, B.I. Kistyakovsky, are considered representatives of both states.